2022
DOI: 10.1038/s41598-022-24030-x
|View full text |Cite
|
Sign up to set email alerts
|

One pot synthesis of two potent Ag(I) complexes with quinoxaline ligand, X-ray structure, Hirshfeld analysis, antimicrobial, and antitumor investigations

Abstract: In one pot, the self-assembly of AgNO3 and 2-chloroquinoxaline (2Cl-quinox) in water–ethanol mixture afforded two novel crystalline Ag(I) complexes. The major product is the polymeric complex [Ag(2Cl-quinox)(NO3)]n; (1), while the minor product (2) comprises two molecules which are the monomeric [Ag(2Cl-quinox)2(NO3)]; (2a) and polymeric [Ag(2Cl-quinox)(NO3)]n; (2b) complexes. The single crystal X-ray structure revealed that 1 and 2b are made up of two-dimensional infinite sheets. In contrast, 2a is a monomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…The coordination chemistry of physiologically and pharmacologically active silver(I) compounds is a subject of extensive research, where several silver(I) complexes have been demonstrated as excellent anticancer, antibacterial, or anti-inflammatory substances [1][2][3][4][5][6][7][8][9][10]. In particular, it is generally recognized that Ag(I) either in the form of silver salts or coordination compounds, could be used medicinally to treat microbial infections resulting from chronic burns or serious wounds [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The coordination chemistry of physiologically and pharmacologically active silver(I) compounds is a subject of extensive research, where several silver(I) complexes have been demonstrated as excellent anticancer, antibacterial, or anti-inflammatory substances [1][2][3][4][5][6][7][8][9][10]. In particular, it is generally recognized that Ag(I) either in the form of silver salts or coordination compounds, could be used medicinally to treat microbial infections resulting from chronic burns or serious wounds [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The biological and pharmacological properties of silver(I) compounds attracted the attention of researchers working on coordination chemistry where numerous Ag(I) complexes had been proven to be anti-inflammatory, anti-tumor, or antibacterial compounds [1][2][3][4][5][6][7][8][9][10]. Particularly, the medicinal use of silver against local infections, whether in the form of inorganic salts or coordination compounds, is extensively approved [11,12].…”
Section: Introductionmentioning
confidence: 99%